A cross sectional study of alcohol consumption among tribal and non-tribal adults of Narayanganj block in Mandla district of Madhya Pradesh, India - Kumar, Rahul Kewal; Tiwari, Rajesh (International Journal Of Community Medicine And Public Health, 2017)
Background: Alcohol consumption is widely prevalent habit among tribal & non-tribal. Awareness about its hazardous effects is important to reduce the number of alcohol users and its dependency in them. A main objective of the study is to find out the magnitude of alcohol consumption among tribal & non-tribal & its association with hypertension. Methods:A cross sectional study using Multi stage sampling method with house to house visits. Sample size came out 300 each from the tribal & non-tribal adults. Study was conducted in Narayanganj block of Mandla district. Results: Among tribal study subjects about 29.3% of the subjects consumed alcohol whereas in non-tribal this was 14.3% & this difference was found to be statistically significant (P<0.0001) (χ2=28.04, P<0.001;OR=2.90 (95%CI= 1.90-4.43)). The difference between Audit score between tribal & non-tribal was found to be statistically significant (P<0.05). Association of hypertension with alcohol among tribal & non-tribal which was significant (χ2 tribal vs. non-tribal=9.22, P=0.0023). Conclusions:Our study shows that the habit of alcohol consumption, AUDIT score & association between alcohol consumption & hypertension was more among tribal.